Junctional adhesion molecule‐A is down‐regulated in anaplastic thyroid carcinomas and reduces cancer cell aggressiveness by modulating p53 and GSK3 α/β pathways. Issue 7 (4th March 2019) - Orlandella, Francesca Maria; Mariniello, Raffaela Mariarosaria; Iervolino, Paola Lucia Chiara; Auletta, Luigi; De Stefano, Anna Elisa; Ugolini, Clara; Greco, Adelaide; Mirabelli, Peppino; Pane, Katia; Franzese, Monica; Denaro, Maria; Basolo, Fulvio; et al.
Abstract: Junctional adhesion molecule A (JAM‐A) is a transmembrane protein that contributes to different biological process, including the epithelial to mesenchymal transition (EMT). Through an EMT profiler array, we explored the molecular players associated with human thyroid cancer progression and identified JAM‐A as one of the genes mostly deregulated. The quantitative real‐time polymerase chain reaction and immunohistochemistry analyses showed that downregulation of JAM‐A occurred in anaplastic thyroid carcinoma (ATC) compared with normal thyroid (NT) and papillary thyroid carcinoma (PTC) tissues and correlated with extrathyroid infiltration, tumor size, and ATC histotype. In ATC cell lines, JAM‐A restoration suppressed malignant hallmarks of transformation including cell proliferation, motility, and transendothelial migration. Accordingly, knockdown of JAM‐A enhanced thyroid cancer cell proliferation and motility in PTC cells. Through the proteome profiler human phospho‐kinase array, we demonstrated that higher expression of JAM‐A was associated with a significant increased level of phosphorylation of p53 and GSK3 α/β proteins. In conclusion, our findings highlight a novel role of JAM‐A in thyroid cancer progression and suggest that JAM‐A restoration could have potential clinical relevance in thyroid cancer treatment.